Student Teachers’ Acceptance towards Blended Learning in Teaching and Learning Psycholinguistics - Rosmania Rima (Universitas Mathla'ul Anwar Banten, 2020)
This study aimed at examining student teachers’ acceptance toward blended learning in teaching and learning Psycholinguistics. It focuses on students’ attitudes toward using SPADA at spada.untirta.ac.id as learning management system combined with face to face learning. The survey involves 118 undergraduate students enrolled in Psycholinguistics course of English Department Untirta. Technological Acceptance Model (TAM), questionaire and interview are used to obtain the data. The learners’ acceptance toward the blended learning in Psycholinguistics course in overall is at a very good level, including the perceived usefulness and the perceived ease of use. For further research, it is suggested to explore the factors that influence teachers' acceptance with blended learning and the proportion between online and face to face learning.